Abnormal movements induced by methanol toxicity. Issue 1106 (30th June 2017) - Rohani, Mohammad; Munhoz, Renato P; Haeri, Ghazal
ABSTRACT: A 22-year-old man came to our clinic with abnormal movements. Five years earlier, he was admitted to the intensive care unit in a coma due to methanol intoxication after drinking significant amount of home-made liquor. He was discharged 4 months later with binocular blindness, slowing of movements and abnormal limb postures. Treatment with trihexyphenidyl and amantadine induced partial improvement of his abnormal movements. On examination, he was fully oriented, speech was slurred and had low tone, visual acuity was in the range of hand motion and both optic discs were atrophied with dilated non-reactive pupils. He had rigidity, hypokinaesia, severe dystonic posture of upper (more on the left side) and lower extremities (more severe on the right side) (see video 1 ) and slow gait. Brain MRI showed bilateral putaminal hyperintensities consistent with necrosis and degeneration (figure 1 ).